2021
DOI: 10.1002/ldr.4122
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic variability of soil diazotrophs in bulk‐rhizosphere and phenological stages under long‐term mulching in an eroded area in the Loess Plateau

Abstract: Free‐living diazotrophs play a significant role in the process of soil biological nitrogen fixation. Long‐term field management has a cumulative effect on soil microbial communities. However, after long‐term mulching measures in erosion areas, the stability difference in diazotrophs in bulk‐rhizosphere soil and the temporal dynamic changes remain unclear. In this study, we analysed the dynamic variability of soil diazotrophic community structures using high‐throughput sequencing. The result of Chao1 diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Keystone taxa have an essential role in governing the microbial community structure and function (Hartman et al, 2018). In our work, we noted that the keystone taxa changed from Proteobacteria and Actinobacteriota at jointing period to Proteobacteria at flowering period, revealing that with the progress of growth, the microbial network structure changed dynamically with changes in soil nutrients (Hao, Zhang, et al, 2021). Interestingly, we also confirmed that FM significantly enhanced the abundance of keystone taxa in the three compartments than non‐mulching at both periods of proso millet.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Keystone taxa have an essential role in governing the microbial community structure and function (Hartman et al, 2018). In our work, we noted that the keystone taxa changed from Proteobacteria and Actinobacteriota at jointing period to Proteobacteria at flowering period, revealing that with the progress of growth, the microbial network structure changed dynamically with changes in soil nutrients (Hao, Zhang, et al, 2021). Interestingly, we also confirmed that FM significantly enhanced the abundance of keystone taxa in the three compartments than non‐mulching at both periods of proso millet.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, we identified that the alpha diversities of the bulk soil were always the highest, followed by that of the rhizosphere soil and root compartments regardless of mulching regime; this phenomenon is very common and has been widely demonstrated in farmland ecosystems (Fan et al, 2018; Hao, Zhang, et al, 2021; Peiffer et al, 2013; Wu et al, 2021). This may be attributed to the reason that when the rhizosphere is close to the root surface, root exudates activated specific microbial species from the bulk soil microbial seed bank (Liu et al, 2020; Schlemper et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations